Parâmetros morfológicos e morfométricos como indicadores da magnitude das corridas de detritos na Serra do Mar Paulista - Vivian Cristina Dias; Bianca Carvalho Vieira; Marcelo Fischer Gramani (Confins)
The main objective of this research was analyze and morphological morphometric parameters watersheds influence in debris flows magnitude occurred in the 1967’s event in Caraguatatuba city, Sao Paulo State, Brazil. Were made (a) the mapping, classification and analysis of the debris flow deposits; and (b) the watersheds morphological and morphometric and parameters analysis, considering the relevance of debris flows occurrence. The results confirmed the influence these parameters in the debris flows magnitude and frequency, namely the circularity ratio and slope.